(untitled) (Journal of Libya for geographical studies, 2025)
This study aimed to assess land degradation in the Wadi Ghabin Basin using Geographic Information Systems (GIS) and Remote Sensing (RS) techniques, based on satellite imagery from Landsat-5 and Landsat-8 sensors (TM and OLI) for the years 2004 and 2024. Spectral indices were applied to detect changes in land degradation, including the Normalized Difference Vegetation Index (NDVI), Crust Index (CI), Drought Barren Soil Index (DBSI), and Land Degradation Index (LDI). The study employed historical, descriptive-analytical, and quantitative methods to process and analyze freely available satellite data from the US Geological Survey (USGS). The results showed significant changes in land degradation over the period. In 2024, the NDVI indicated the largest area of bare lands classified as severely degraded, covering approximately 450.94 km² (99.54% of the total area), marking an increase of 25.6% compared to 2004. The DBSI showed severe erosion degradation over 380.04 km² (83.89% of the area), which is 61.86% higher than in 2004, mainly due to rising temperatures, reduced rainfall, and diminished vegetation cover. The LDI revealed moderate soil degradation over 323.21 km² (71.35%), an increase of 38.8% from 2004, attributed to intensified wind erosion resulting from low rainfall, reduced vegetation, and higher temperatures.